Nature in Some Selected Poems of Keats and Al-Shabbi - Yazid Meftah Ali Wahas; Ahmed Taher Abdu Nagi (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This study is a novel attempt to examine the theme of nature in the poetry of John Keats and Abu Al-Qasim Al-Shabbi since nature is of great importance in Romantic poetry whether Arabic or English. The objective of the present study is to investigate the concept of nature in some selected poems by Keats and Al-Shabbi. The study has proposed that there is a relationship between nature in Arabic poetry and English poetry since Al-Shabbi was influenced by English romantics like Wordsworth, Shelley and Keats through some translations of their poetry. Keats and Al-Shabbi are celebrated poets in English and Arabic Romantic literature. Although they died young at 25 and had only a few years of experience with poetry, they wrote the most beautiful poems that revealed their poetic abilities which were sufficient to rank them among the greatest poets. The study has adopted the qualitative, analytical and comparative approach. The study concluded that there is a similarity between Al-Shabbi and Keats because they belong to the same poetic trend. For Keats, the natural world represents an ideal environment and a source of beauty and truth. For Al-Shabbi, nature represents the spiritual unity between man and nature and a refuge from the cruelty of the city and the anxieties of life. Both Keats and Al-Shabbi found a solace in nature due to their identical suffering; Keats of physical illness of TB and Al-Shabbi of heart disease. Accordingly, they escaped to nature to forget their worries.